Incongruent visual feedback during a postural task enhances cortical alpha and beta modulation in patients with Parkinson's disease. Issue 7 (July 2018) - van den Heuvel, Maarten R.C.; van Wegen, Erwin E.H.; Beek, Peter J.; Kwakkel, Gert; Daffertshofer, Andreas
Highlights: Parkinson's disease (PD) patients rely more on visual information than healthy controls when controlling their balance. We determined cortical activity with event-related EEG during a weight-shifting task with (in)congruent visual feedback. Alpha/beta modulation in primary visual/motor areas discriminated between PD and controls. Abstract: Objective: In patients with Parkinson's disease (PD), augmented visual feedback (VF) can improve functional motor performance. Conversely, they appear to rely more on visual information than healthy subjects, which is unfavorable when this information is unreliable. Cortical beta activity is thought to be associated with the need for motor adaptation. We here compared event-related EEG parameters during a whole-body postural weight-shifting task between congruent and incongruent feedback conditions. Methods: Twenty-four patients with PD and fifteen healthy, age- and gender-matched controls performed rhythmic swaying movements. VF was presented in real-time (congruent), delayed (incongruent), or was entirely absent. We estimated source activity in four regions-of-interest and determined motor-related spectral power and power modulation in alpha and beta frequency bands. Results: For congruent VF no significant differences in cortical activity between the two groups were present. For incongruent VF, the PD group showed significantly higher beta modulation in primary motor cortex, and higher alpha modulation in primary visual cortex. Conclusions: Event-related beta modulation in the motor network and alpha modulation in visual areas discriminated between groups, suggesting altered visuomotor processing in PD patients. Significance: This study finds evidence for increased modulation of alpha/beta activity during perceptual-motor tasks in PD, possibly indicating an unwarranted higher confidence in VF.